2014
DOI: 10.3415/vcot-13-12-0145
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiographic measurements of the patellar tendon-tibial plateau angle with anatomical measurements in dogs

Abstract: Both the common tangent and conventional methods show poor concordance with the anatomical measurement of PTA. Further studies are needed to determine if errors in measurements affect the clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
3
0
2
Order By: Relevance
“…The ML projection was obtained with a stifle joint angle of 135°and with a superimposition of femoral condyles. Using a medical image viewer (Horos software, Lesser General Public License Version 3.0, LGPL 3.0, in Horosproject.org), the amount of advancement required in each case was determined by common tangent method [42][43][44][45]. The OA stage was determined in each stifle with the Bioarth Scale [24].…”
Section: Surgical Techniquementioning
confidence: 99%
“…The ML projection was obtained with a stifle joint angle of 135°and with a superimposition of femoral condyles. Using a medical image viewer (Horos software, Lesser General Public License Version 3.0, LGPL 3.0, in Horosproject.org), the amount of advancement required in each case was determined by common tangent method [42][43][44][45]. The OA stage was determined in each stifle with the Bioarth Scale [24].…”
Section: Surgical Techniquementioning
confidence: 99%
“…The authors cited that both methods can be used but indicated a preference for the common tangent at the tibiofemoral contact point method (Schwandt et al 2006). In another study, the patellar ligament angle values obtained by the common tangent method were lower than the anatomical patellar ligament measurements and conversely, those obtained by conventional method were systematically higher (Bismuth et al 2014). In the current study, the mean of these angles was significantly higher when obtained using the tibial plateau method compared with the common tangent method.…”
Section: Discussionmentioning
confidence: 99%
“…Rzeczywisty przebieg plateau kości piszczelowej ma ogromne znacznie podczas określania kąta inklinacji więzadła prostego rzepki (patellar tendon angle -PTA), wykorzystywanego w procedurze wysunięcia guzowatości kości piszczelowej (TTA -tibial tuberosity advancement) oraz jej modyfikacjach (TTA Rapid) (7,12,15,17,37), a wartość TPA wyższa niż 30° sprawia, że metoda nie jest odpowiednio skuteczna (8,20).…”
Section: Zastosowanie Pomiaruunclassified
“…Ze względu na nie w pełni zrozumiały wpływ kąta nachylenia plateau na uszkodzenie więzadła krzyżowe-go doczaszkowego dokonywano kolejnych pomiarów, określając nowe wartość charakteryzujące bliższą części kości piszczelowej, do których należą: długość plateau kości piszczelowej, kąt nachylenia więzadła prostego rzepki w stosunku do plateau kości piszczelowej (patella tendon angle -PTA), szerokość względna guzowatości kości piszczelowej (relative tibial tuberosity width -rTTW), kąt nachylenia osi bliższego końca kości piszczelowej (distal tibial axis/proximal tibial axis angle DPA, kąt Z (Z angle), Wykorzystywano również do pomiarów linię Blumensaata (5,7,12,23,33,43,45,50,63).…”
Section: Inne Pomiaryunclassified